Psychoeducational programmes for family caregivers of the person with a mental health condition: a scoping review - Isabel Escrivães da Costa; Ana Barreira; Rosa Silva; Carlos Sequeira (Instituto Politécnico de Viseu, 2024)
Introduction: The inability of the family caregiver of a person with a mental health condition to perform their role implies that care provided is done by health institutions, with which added costs are associated. Therefore, it is fundamental to empower these caregivers by implementing psychoeducational programs. These programs are a form of mental health education aimed at equipping individuals with knowledge through an educational component combined with emotional support. Objective: To map, analyze, and summarise the psychoeducational programs of the family caregiver of a person with mental health and/or psychiatric disorder developed in the Portuguese context. Methods:  The methodological steps of the scoping review according to the JBI were followed. The search was carried out in several databases, such as CINAHL, Academic Search Complete, Educational Resource Information Center (ERIC), Medline Complete, and Psychology and Behavioral Sciences Collection (all of which through EBSCOhost). As a source of grey literature, the Repositórios Científicos Abertos de Portugal (RCAAP) was used. Results: Eight psychoeducational programs, with two large groups established: family caregivers of people with dementia and family caregivers of people with schizophrenia. Conclusions: It is necessary to validate already established psychoeducational programs, as well as systematizing the information provided/extracted from them, to implement the best scientific evidence. This review serves as a reference document for family caregiver programs, suggesting further research in the future to also include international programs.